2011
DOI: 10.5195/jyd.2011.179
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Role of Youth Workers

Abstract: Abstract:In reviewing the field of youth development, of which youth workers are a part, it is clear it has had a long and complex history that is intertwined with other disciplines. More recently youth workers have experienced a transformation of sorts, with youth programs in the past being seen exclusively as a place to play and have fun, whereas today's expectations include a much broader focus on the overall positive development of young people. This evolution has been heavily influenced by a number of soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Generally, enterprises determine the appropriate content for training programmes (or training activities) to enhance the professional development of staff. For instance, training programmes for new employees, training programmes for senior managers, multicultural or cross-cultural education and training, security training, and occupational health training [62,63]. To understand the current status of training activities, we will analyse them from four aspects: training content, training managers, training staff and training format.…”
Section: Identification Of Employee Training Activities and Abstractmentioning
confidence: 99%
“…Generally, enterprises determine the appropriate content for training programmes (or training activities) to enhance the professional development of staff. For instance, training programmes for new employees, training programmes for senior managers, multicultural or cross-cultural education and training, security training, and occupational health training [62,63]. To understand the current status of training activities, we will analyse them from four aspects: training content, training managers, training staff and training format.…”
Section: Identification Of Employee Training Activities and Abstractmentioning
confidence: 99%
“…While several scholars recommend OST staff are trained to respond to the dynamic nature of the OST context (e.g., Borden, et al, 2004;Larson, et al, 2009;Rhodes, 2004), this study demonstrated that training staff to engage an ethic of care has limitations. Little is known about effective staff training mechanisms in youth programs in general (Shek, & Wai, 2008), yet OST programs increasingly rely on staff to promote a myriad youth development goals (Borden, Schlomer, & Wiggs, 2004). Practitioners should make provisions for staff members' developmental readiness to adopt an ethic of care or other areas of "expertise" that might improve staff-youth interactions at the point of service.…”
Section: Discussionmentioning
confidence: 74%
“…Youth workers can go beyond promoting a young person's development in typical ways (e.g., supporting academic success, reducing risk-taking behaviors, increasing positive health attitudes) (Borden, Schlomer, & Wiggs, 2011) to providing social and physical environments that support healthful behaviors and effectively guiding youth who want to advocate for healthier communities. To better support youth as health advocates, youth workers can look to many existing PYDH competency-building resources (see Table 1).…”
Section: Health Advocacymentioning
confidence: 99%